ISLAMIC WORLDVIEW IN THE PERSPECTIVE OF M.T.M YAZDĪ AND S.M.N AL-ATTAS AND THEIR IMPLICATION ON ISLAMIZATION OF KNOWLEDGE - Ahmad Sulaiman (Sekolah Tinggi Agama Islam Sadra, 2023)
The stagnant and even underdeveloped condition of Muslims all over the world has raised concerns among scholars. Many are trying to offer solutions to restore Islamic civilization to its peak. Various proposals lead to the reconstruction of philosophical elements, including epistemology and worldview, to more practical ones, such as the Islamization of knowledge. This study tries to compare the concept of worldview and its implications for the Islamization of knowledge from two major contemporary figures. The two are Syed Muhammad Naquib Al-Attas, a mainstream leader of the Islamization of knowledge from Malaysia, and Ayatullah Muhammad Taqie Miṣbāḥ Yazdī, a neo-Sadrian philosopher from Persia. This research used a qualitative approach, namely the method of literature study to understand the Islamic worldview from the perspective of the two figures and what the implications are for the Islamization of knowledge. The results of the study revealed they both believe in the importance of a genuine worldview as the basis for the reconstruction of Muslims at the individual level and Islam at the level of civilization. However, they adhere to different ontological and epistemological arguments. In Al-Attas, the commitment to sacred texts as well as the interpretation of classical scholars makes the model of Islamization of knowledge tend to be backward and reactionary towards the West. As for Ayatullah Yazdī, prioritizing reason and demonstration has led to a model of Islamization of science that is critical and open for dialogue toward Western science.